2020
DOI: 10.1089/lap.2020.0119
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Liver Resections: Application of Difficulty Score Systems to an Initial Experience. Is a Specific Robotic Difficulty Score Necessary?

Abstract: Background: Recently, the minimally invasive surgical approach has been available for performing liver resections (LRs) with laparoscopic and robotic techniques. The robotic approach for LRs seems to overcome several laparoscopic limitations, which is a valid alternative when performed in high volume and specialized centers. Laparoscopic difficulty score systems (DSSs) should serve to guide the surgeon's choice in the best surgical approach to adopt for every single patient, giving the possibility to switch to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Of note, as for surgical procedures, the use of MIS is predominantly still limited to minor surgeries, mostly in the context of wedge resection or isolated segmentectomy of anterolateral segments and left lateral sectionectomy 3,9,10,29–31 . In this scenario, the use of robotic platforms has been proposed to overcome some of the technical limitations of conventional laparoscopy and widen the application of MIS for liver surgery 3,6,28,31–38 . The difficulties in liver exposition, parenchymal frailty, the risk of bleeding limited laparoscopy application in liver surgery to selected patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, as for surgical procedures, the use of MIS is predominantly still limited to minor surgeries, mostly in the context of wedge resection or isolated segmentectomy of anterolateral segments and left lateral sectionectomy 3,9,10,29–31 . In this scenario, the use of robotic platforms has been proposed to overcome some of the technical limitations of conventional laparoscopy and widen the application of MIS for liver surgery 3,6,28,31–38 . The difficulties in liver exposition, parenchymal frailty, the risk of bleeding limited laparoscopy application in liver surgery to selected patients.…”
Section: Discussionmentioning
confidence: 99%
“…3,9,10,[29][30][31] In this scenario, the use of robotic platforms has been proposed to overcome some of the technical limitations of conventional laparoscopy and widen the application of MIS for liver surgery. 3,6,28,[31][32][33][34][35][36][37][38] The difficulties in liver exposition, parenchymal frailty, the risk of bleeding limited laparoscopy application in liver surgery to selected patients. Robotic technology has made it possible to overcome many of the limitations of laparoscopic surgery, which include a reduction in tremors, magnifying images with three-dimensional technology, an increase in the effectiveness of surgical gestures through tools with several degrees of freedom and an improvement in fatigue in relation to the continuation of surgery.…”
Section: Authormentioning
confidence: 99%
“…[44][45][46] Two articles were excluded by virtue of them being review articles with no unique datasets 10,46 and one article was found to be a duplicate, 19 and the remaining 37 articles were included in the qualitative analysis. 3,[6][7][8][9][11][12][13][14]17,18,…”
Section: Literature Searchmentioning
confidence: 99%
“…Twelve studies in the literature had supporting data for the Iwate DSS for MILR. [11][12][13]18,32,[33][34][35][36][37][38][39] Notably, the Iwate DSS was not formulated based on any data but as a modification of the Ban DSS based on expert opinion. Ten studies had supporting data for Iwate DSS for LLR against various outcome measures, 11,12,18,[32][33][34][35][36]38,39 of which eight studies 11,12,18,21,[32][33][34][35][36] published data that was amenable to pooling (Table 3).…”
Section: Iwate Dssmentioning
confidence: 99%
See 1 more Smart Citation